Benefits of physical exercise on soil and liquid means on pain in obesity - Castanho, Conrado Pizzolatto; Soares, Thaise Dutra; Moraes, Fernanda Caetano; Barcellos, Maria Augusta; Nass, Stéphany Rittes; Branco, Jerônimo (Disciplinarum Scientia | Saúde, 2019)
Being overweight causes consecutive episodes of pain. One of the most important methods for prevention and treatment of pain of obese people is physical exercises. The objective of this work is to search for the literature on the benefits of physical exercise, performed in soil and in the liquid medium on the context of pain in obese individuals. A literature search was conducted at the end of 2018 and early 2019. The articles that make up this review were accessed in the Lilacs, Scielo and Pubmed databases. The descriptors used as basis for the research were: Water exercise and obesity and pain / Exercise and obesity and pain, respecting as inclusion criteria the studies that highlighted the benefits of physical exercise in soil and in the liquid medium and that presented a relationship with pain and obesity. And as exclusion criteria, studies that did not provide information on the association of obesity with physical exercise and pain in the title, abstracts that did not present prominent data, and studies that did not provide important results after reading the full text. A total of 689 studies were found and only 47 were selected, of which 16 were Portuguese and 31 were English (English), between 2002 and 2019. The studies found important benefits of physical exercise, mainly performed in a liquid environment, thus showing that obese people tend to avoid consecutive episodes of pain with exercise.